The association between diet and serum concentrations of IGF-I, IGFBP-1, IGFBP-2, and IGFBP-3 in the European prospective investigation into cancer and nutrition - Crowe, F; Key, T; Allen, N; Appleby, P; Roddam, A; Overvad, K; Grønbæk, H; Tjønneland, A; Halkjær, J; Dossus, L; Boeing, H; Kröger, J; et al. (2009)
Circulating concentrations of insulin-like growth factor I (IGF-I) and IGF binding proteins (IGFBP) have been associated with the risk of several types of cancer. Dietary correlates of IGF-I and IGFBPs are not yet well established. The objective of this study was to assess the association between dietary intake and serum concentrations of IGF-I, IGFBP-1, IGFBP-2, and IGFBP-3 in a cross-sectional analysis of 4,731 men and women taking part in the European Prospective Investigation into Cancer and Nutrition. Diet was assessed using country-specific validated dietary questionnaires. Serum concentrations of IGF-I, IGFBP-1, IGFBP-2 and IGFBP-3 were measured, and the associations between diet and IGF-I and IGFBPs were assessed using multiple linear regression adjusting for sex, age, body mass index, smoking status, and alcohol and energy intake. Each 1 SD increment increase in total and dairy protein and calcium intake was associated with an increase in IGF-I concentration of 2.5%, 2.4%, and 3.3%, respectively (P for trend <0.001 for all) and a decrease in IGFBP-2 of 3.5%, 3.5%, and 5.4% (P for trend <0.001 for all), respectively. There were no significant associations between the intake of protein or calcium from nondairy sources and IGF-I. The results from this large cross-sectional analysis show that either the intake of dairy protein or calcium is an important dietary determinant of IGF-I and IGFBP-2 concentrations; however, we suggest that it is more likely to be protein from dairy products. Copyright © 2009 American Association for Cancer Research.